The absence of God in modernist literature - Erickson, Gregory (Palgrave Macmillan, 2007)
This book combines literary criticism, postmodern theology, philosophy, and musicology in a rethinking of the relationship of modernist literature and religion. Erickson argues that theological modes of thinking are ingrained in the very roots of our metaphysical assumptions, and are impossible to escape, even and especially in the skeptical and experimental woks of modernism. By concentrating on moments of difficulty and ambiguity in works such as Henry James?s The Golden Bowl, Marcel Proust?s In Search of Lost Time, and Arnold Schoenberg?s opera Moses und Aron, the book identifies the paradoxical construction of a god-idea buried in the tropes and metaphors of each text.